METHODOLOGY OF USING INNOVATIVE APPROACHES IN DEVELOPING MATHEMATICAL CREATIVITY OF HIGH SCHOOL STUDENTS - Absoatov Ulugbek Kadirovich (Bright Mind Publishing, 2025)
This article scientifically reveals educational methods aimed at developing mathematical creativity of high school students in the process of teaching mathematics and their effectiveness.
Keywords: Mathematical creativity, Interactive approach, ensuring freedom of thought, encouraging participation, effective use, participatory and motivating, Interactive whiteboard, GeoGebra or Desmos.